2009
DOI: 10.1158/1535-7163.mct-08-0890
|View full text |Cite
|
Sign up to set email alerts
|

Biological characterization of AT7519, a small-molecule inhibitor of cyclin-dependent kinases, in human tumor cell lines

Abstract: Cyclin-dependent kinases (CDK), and their regulatory cyclin partners, play a central role in eukaryotic cell growth, division, and death. This key role in cell cycle progression, as well as their deregulation in several human cancers, makes them attractive therapeutic targets in oncology. A series of CDK inhibitors was developed using Astex's fragment-based medicinal chemistry approach, linked to high-throughput X-ray crystallography. A compound from this series, designated AT7519, is currently in early-phase … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(103 citation statements)
references
References 36 publications
6
97
0
Order By: Relevance
“…In this latter model, following the guidelines used by clinicians to score response in solid tumors (39), we observed not only stasis but also tumor regression (with a "partial response" in 20-50% of evaluated tumors) and we believe this may be a significant finding in comparison with other latest-generation CDKIs. Several "evolved" CDK2 inhibitors, such as R547 (40), P276-00 (41), AT7519 (42), and AZD5438 (43), are reported to be in late preclinical or clinical testing, but we believe PHA-848125 is unique in possessing the combined properties reported here of good oral bioavailability, capacity to induce tumor regression, and flexibility of treatment scheduling, as shown in the DMBA-induced mammary carcinoma model. Notably, in all preclinical efficacy experiments, PHA-848125 was well tolerated without overt signs of toxicity.…”
Section: Discussionmentioning
confidence: 83%
“…In this latter model, following the guidelines used by clinicians to score response in solid tumors (39), we observed not only stasis but also tumor regression (with a "partial response" in 20-50% of evaluated tumors) and we believe this may be a significant finding in comparison with other latest-generation CDKIs. Several "evolved" CDK2 inhibitors, such as R547 (40), P276-00 (41), AT7519 (42), and AZD5438 (43), are reported to be in late preclinical or clinical testing, but we believe PHA-848125 is unique in possessing the combined properties reported here of good oral bioavailability, capacity to induce tumor regression, and flexibility of treatment scheduling, as shown in the DMBA-induced mammary carcinoma model. Notably, in all preclinical efficacy experiments, PHA-848125 was well tolerated without overt signs of toxicity.…”
Section: Discussionmentioning
confidence: 83%
“…AT7519 was rationally designed with the use of high throughput X-ray crystallography (1), and its activity has been evaluated in preclinical models (2) and a phase I clinical trial in refractory solid tumors (3). Recently, the role of cdks 7, 8, and 9 in the regulation of transcription has been explored (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…We observed in solid tumor lines that AT7519 is in addition a potent inhibitor of transcription (2). Based on the transcriptional activity of AT7519, we hypothesized that it would promote apoptosis in leukemia cell lines and chronic lymphocytic leukemia (CLL) cells through this mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we have studied the GSK-3β pathway (known to have a crucial role in several signaling cascades relevant to MM biology), in the context of CDK inhibition, exploring the pharmacology of AT7519, a multi-targeted CDK inhibitor, that potently inhibits CDK1, 2, 4, 6, 7, 9. 12,61,62 The drug has shown potent anti-MM activity both in vitro and in vivo. In addition, molecular studies of AT7519 revealed that GSK-3β has a crucial role in AT7519-mediated antimyeloma effect.…”
Section: Do Not Distributementioning
confidence: 99%